A Student-Centered Teaching and Learning Approach Among Excellent Teachers of Islamic Education - Kamarul Azmi Jasmi; Rasidah bt Sahran; Muhamad Amirul Amin Mohamad Nazim (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The role of Islamic Education teachers in imparting knowledge needs to be refined in line with the transformation of the country's education. The implementation of a student-centered teaching and learning approach can have a positive impact on students in improving the quality of knowledge achievement. Therefore, teachers need to equip itself with various pedagogical knowledge, especially student-centered teaching and learning. The purpose of this writing is to explore the student-centered teaching and learning approach among excellent teachers of Islamic education in secondary schools. This writing is done through a qualitative research methodology using interview data as the main data and supported by observation data and document analysis. Excellent teachers of Islamic education selected from eight schools are study participants along with 40 study informants. Along with interview data, there are eight observation data and eight document analysis data. All 56 verbatim were compiled and analyzed using NVivo 20 software to build themes and sub-themes of research findings. The results of the study show that there are 22 student-centered teaching and learning methods and techniques that form a pattern. This finding can produce a Student-Centered teaching and learning approach Model among Excellent teachers of Islamic education in secondary schools.